Meningkatkan Semangat Minat Belajar Al-Qur'an pada Anak di Panti Asuhan Al-Jami'yatul Washliyah - Liza Afilia Suryani; Husni Thamrin (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Interest in reading needs to be instilled and grown since children are small because interest in reading in children will not be formed by itself, but is strongly influenced by stimuli obtained from the child’s environment. Especially the interest in learning to read the Qur’an which is the main guideline for Muslims. The purpose of this research is to increase the spirit of interest in learning the Qur’an in children at the Al-Jami’yatul Washliyah Orphanage. The intervention rogram is carried out using the Mezzo Intervention by Zastrow which consist of Engagement, Intake and Contract, Assessment, Planning, Intervention, Evaluation and Termination. The final results obtained are that children become more aware and understand in learning to read the Qur’an.